Kontroversi Al-‘Umran: Ibn Khaldun dan Perdebatan Klaim Kebaruan - Abdul Kadir Riyadi (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
Ibn Khaldun is one of the monumental Muslim Arab scholars. He inherited scholarly blueprint recognized not only in the Muslim world but also in the world in general. However several of his ideas and thoughts have not been fully explored. One of them is his concept of al-'Umran which he claimed as a new concept he found. The concept of al-'Umran is a science of social organization, which described the idea of society and its essential characteristics. Some of the scholars comprehended al-'Umran as a cultural science, not as a sociological science. This article is to examine Ibnu Khaldun’s concept of al-'Umran and its claim of a new contribution and to understand Ibn Khaldun’s theory of al-'Umran and its originality. This research employs analytical study to the contemporary Arab Muslim's through on this matter. The research reports that the modern Arab Muslim's opinion in regards to the concept al-'Umran is divided into three categories: 1) Those who support the originality of his concept. 2). Those who reject the originality of his idea. 3). Those who develop and reinterpret the concept of al-'Umran.